Beyond the Story Itself: Narrative Inquiry and Autoethnography in Intercultural Research in Higher Education - Sheila Trahar (Forum: Qualitative Social Research, 2009)
STENHOUSE's (1981) differentiation between research on education and research in education contributed much to the development of practitioner research in educational settings, yet exemplars of university teachers researching their own practice are rare. Even rarer, in spite of pleas from "international students" for reciprocal dialogue with local academics and students to recognise the value of many different realities and knowledges (KOEHNE, 2006), are practitioners who reflect critically on the personal and professional impact of cultural diversity in higher education (BRUNNER, 2006). In this article, I critique how a narrative inquiry paradigm supported and challenged me to explore different realities and knowledges about learning and teaching in a UK higher education context in my doctoral research with postgraduate students from many different cultures. Practitioner research is, inevitably, an iterative process—research and practice are inextricably linked and continuously evolving. Thus, through the autoethnographic exploration of my own practice, my "subject positions, social locations, interpretations, and personal experiences" continue to be examined "through the refracted medium of narrators' voices" (CHASE, 2005, p.666), glimpses of which will be seen as the article unfolds. URN: urn:nbn:de:0114-fqs0901308